Using textbook outcome as a measure of quality of care in oesophagogastric cancer surgery. Issue 5 (21st February 2018) - van der Kaaij, R T; de Rooij, M V; van Coevorden, F; Voncken, F E M; Snaebjornsson, P; Boot, H; van Sandick, J W
Abstract: Background: Textbook outcome is a multidimensional measure representing an ideal course after oesophagogastric cancer surgery. It comprises ten perioperative quality-of-care parameters and has been developed recently using population-based data. Its association with long-term outcome is unknown. The objectives of this study were to validate the clinical relevance of textbook outcome at a hospital level, and to assess its relation with long-term survival after treatment for oesophagogastric cancer. Methods: All patients with oesophageal or gastric cancer scheduled for surgery with curative intent between January 2009 and June 2015 were selected from an institutional database. A Cox model was used to study the association between textbook outcome and survival. Results: A textbook outcome was achieved in 58 of 144 patients (40·3 per cent) with oesophageal cancer and in 48 of 105 (45·7 per cent) with gastric cancer. Factors associated with not achieving a textbook outcome were failure to achieve a lymph node yield of at least 15 (after oesophagectomy) and postoperative complications of grade II or more. After oesophagectomy, median overall survival was longer for patients with a textbook outcome than for patients without (median not reached versus 33 months; P = 0·012). After gastrectomy, median survival was 54 versus 33 months respectively ( P = 0·018). In multivariable analysis, textbook outcome was associated with overall survival after oesophagectomy (hazard ratio 2·38, 95 per cent c.i. 1·29 to 4·42) and gastrectomy (hazard ratio 2·58, 1·25 to 5·32). Conclusion: Textbook outcome is a clinically relevant measure in patients undergoing oesophagogastric cancer surgery as it can identify underperforming parameters in a hospital setting. Overall survival in patients with a textbook outcome is better than in patients without a textbook outcome. Abstract : Quality of care in one number